Effective Communication during a Global Health Crisis: A Content Analysis of Presidential Addresses on the COVID-19 Pandemic in Ghana (Journal of International Crisis and Risk Communication Research, 2021)
The COVID-19 pandemic is causing incessant disruption to the social and economic lives of societies. Public health and crisis communicators have recommended some best practices in crisis and emergency risk messaging for effective health messages during pandemics. Thus, this study utilized seven crisis and emergency risk messaging best practices to qualitatively analyze 14 speeches delivered by the Ghanaian President on the COVID-19 pandemic in the country to demonstrate how the speeches conveyed information about the pandemic to the public. The study found that all seven best practices (i.e., explain what is known, explain what is not known, explain how or why the event happened, promote action steps, express empathy, express accountability, and express commitment) were demonstrated in all the 14 speeches. Implications for practice are discussed.